Parafiction in Music (Studies): Performance Ethnography beyond the Practice/Performance Turn - Kiwi Menrath, Stefanie (Analitica. Rivista online di studi musicali, 2017)
Through practices of parafiction electronic music culture has advanced critiques of the institutions of pop music. How can academic research learn from such pop music-derived critical practices? Ursula Bogner is a person whose historical existence is unverified: she was a German pioneer of electronic music of the 1960s to 1990s – at least this is purported in the linernotes of compilations of her musical „archive“. Yet even the earliest media discussions of „Ursula Bogner“ already raised the suspicion, that she might not have been a historical person, but rather a collaborative imagination. Ursula Bogner might be described as a „parafiction“, a (musico-)artistic strategy of enmeshing imaginary personalities into the „real“ world for the sake of questioning institutions and epistemologies such as the identificatory system of stardom in pop music which tends to exclude minority (a.o. female) positions. As it becomes an object of research, this music project also calls into question procedures of authorization and implicit epistemologies of academic knowledge production. Ultimately, it calls for an experimental research methodology that is commensurate to its parafictional natur; namely, performance ethnography experiments, in the tradition of activist and performative anthropology, with research practice as performance. This article explores how the epistemological critique of parafiction within electronic music culture can be answered through performative research. The article concludes with an advocation of an ethnographic research format derived from the field: the collaborative investigation of imaginary research objects as a radical implementation of the performative turn in the cultural studies of music.